Pengelolaan Sampah Perkotaan dengan Metode Dinamis di Tempat Pembuangan Akhir (TPA) Bestari Probolinggo - Giovanni Dakpati Mentaya Lukas; Naniek Ratni J.A.R (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Increased waste generation is directly related to the increase in the number of population. Increasing waste generation make this issue needs serious attention from government so that garbage does not piled high in landfill. This study’s purpose  to estimate the reduction of waste generation and the City Probolinggo sourced from city waste for 10 years based on simulation results. Data was analyzed using software stella 9.0. The results that waste was entered to Landfill Bestari Probolinggo is of 0,20 kg/people/day. Waste was dominated by organic waste with a proportion of 73,83%, while the inorganic was amounted to 26,17%. The Recycling Scenario has the largest waste reduction. Waste reduction of Recycling scenario in Probolinggo City in 2032 was increased to 244,09 ton/year (220,09 ton reduction in composting house and 23,17 ton reduction in solid waste banks). The realistic improvement of recycling scenario involved with improvement scenario to added composter and waste banks facilities with comparison 70%:30%. Improvement for the scenario was selected by added composter and costumer of solid waste bank. Individual composter needed as much as 84 units and 570 customers of solid waste bank. In 2032, the addition of these facilities increased the reduction with 475,67 tons/year or 2,19 greater than existing conditions.